Enhancing Customer Loyalty Through Customer Satisfaction of Service Quality and Brand Image in Travel Companies - Ryan Firdiansyah Suryawan; Yosi Pahala; Teguh Maianto; Wenny Desty Febrian (Jurnal Manajemen Industri dan Logistik, 2025)
This study aims to investigate how customer satisfaction affects customer loyalty within the travel agency sector in Indonesia, aiming to address gaps in the current literature. This study analyzes the effect of service quality and brand image on customer satisfaction and loyalty in the travel sector in Indonesia, using a quantitative approach with Structural Equation Modeling (SEM). The research shows that in Indonesia's travel agency industry, a strong brand image greatly enhances customer loyalty and satisfaction with total 30 travel agency companies. Travel companies can cultivate long-term loyalty by prioritizing brand reputation and consistently improving customer satisfaction. all dimensions have been tested for reliability, yielding a value of 0.817, and validity, with all five indicators passing the test. the results of the Customer Satisfaction variable test, revealing a GFI of 0.962 and a reliability score of 0.791. These findings indicate the data's validity and reliability for the subsequent measurement phase.